The Biomechanics of Cervical Spondylosis - Lisa A. Ferrara (Advances in Orthopedics)
Aging is the major risk factor that contributes to the onset of cervical spondylosis. Several acute and chronic symptoms can occur that start with neck pain and may progress into cervical radiculopathy. Eventually, the degenerative cascade causes desiccation of the intervertebral disc resulting in height loss along the ventral margin of the cervical spine. This causes ventral angulation and eventual loss of lordosis, with compression of the neural and vascular structures. The altered posture of the cervical spine will progress into kyphosis and continue if the load balance and lordosis is not restored. The content of this paper will address the physiological and biomechanical pathways leading to cervical spondylosis and the biomechanical principles related to the surgical correction and treatment of kyphotic progression.